Barriers and enablers of women carers from culturally and linguistically diverse communities participating in physical activities - Kappelides, Pam (Frontiers in Sports and Active Living, 2024)
Introduction This research article presents a phenomenological evaluation of an organization working within disability and with CALD communities of a project that was supporting women carers who are newly arrived to Australia to be happier and healthier. The initiative aimed to alleviate social isolation, enhance wellbeing, and boost confidence among women from Culturally and Linguistically Diverse (CALD) backgrounds in Metropolitan Melbourne, Victoria. Methods Through a qualitative exploration of the lived experiences of participants, findings were categorized into enablers and barriers, shedding light on the outcomes of physical activity participation for these women. Results and discussion Enablers included improvements in health, skill development, achievement, and enhanced social interaction and support, while barriers encompassed challenges related to access, socio-cultural factors, resource availability, interpersonal dynamics, and physiological constraints. Based on these findings, recommendations are proposed to empower CALD community members in the co-development and co-delivery of future programs, fostering sustainability and community-driven engagement.